Advances in Fetal Surgery: Current and Future Relevance in Plastic Surgery - Gimenez, Alejandro; Kopkin, Rachel; Chang, Daniel K.; Belfort, Michael; Reece, Edward M. (Seminars in Plastic Surgery, 2019)
Scarless healing has long been the holy grail for plastic surgery. While historically fetal surgery has tempted plastic surgeons with the allure of scarless correction of congenital abnormalities, the risks far outweighed the benefits and these interventions never materialized. Current advances in fetal surgery with minimally invasive fetoscopic surgery have made these early fetal interventions safer, leading to expanding applications. While the plastic surgeon's role is limited as of yet, this article provides a review of the history of fetal surgery and the advances that may become relevant to the future plastic surgeon.
Keywords: fetoscopic surgery; amniotic band syndrome; plastic surgery; reconstructive surgery